2018
DOI: 10.14814/phy2.13638
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional scaling of vocal variability by an avian cortico-basal ganglia circuit

Abstract: Behavioral variability is thought to be critical for trial and error learning, but where such motor exploration is generated in the central nervous system is unclear. The zebra finch songbird species offers a highly appropriate model in which to address this question. The male song is amenable to detailed measurements of variability, while the brain contains an identified cortico‐basal ganglia loop that underlies this behavior. We used pharmacogenetic interventions to separately interrogate cortical and basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…We also found that OR modulation in LMAN and Area X appear to have contrasting effects on the spectral properties of song (Heston et al, 2018). In an earlier study, blocking ORs in Area X led to significant decreases in FM, AM and pitch goodness, and a significant increase in pitch, whereas Wiener entropy and mean frequency of motifs was not affected (Kumar et al, 2019).…”
Section: Changes In or Modulation In Lman Lead To Alterations In The supporting
confidence: 57%
“…We also found that OR modulation in LMAN and Area X appear to have contrasting effects on the spectral properties of song (Heston et al, 2018). In an earlier study, blocking ORs in Area X led to significant decreases in FM, AM and pitch goodness, and a significant increase in pitch, whereas Wiener entropy and mean frequency of motifs was not affected (Kumar et al, 2019).…”
Section: Changes In or Modulation In Lman Lead To Alterations In The supporting
confidence: 57%
“…Female preference for male song is inversely correlated with song variability (Woolley and Doupe, 2008; Chen et al, 2017; Heston et al, 2018). To determine if increased variability of FD song induced by FoxP2 overexpression was perceived by conspecifics, and thus of potential ethological relevance, we tested whether female zebra finches altered their behavior in response to more stereotyped (AAV-FoxP2 PRE FD) or variable (AAV-FoxP2 POST FD) songs.…”
Section: Resultsmentioning
confidence: 99%
“…The zebra finch (Taeniopygia guttata) provides an excellent avian system to understand the neural mechanisms of pair bonding. In addition to the formation of monogamous pairs, their courtship behavior is well described (Zann, 1994(Zann, , 1996, much of the circuitry involved in social behaviors is known (O'Connell and Hofmann, 2011b;Prior and Soma, 2015;Wild and Botelho, 2015) and the system is becoming more accessible to specific neural manipulations (Heston et al, 2018;Murugan et al, 2013;Xiao et al, 2018;Yazaki-Sugiyama et al, 2015). Additionally, previous studies in zebra finches have identified that partner preference is dependent on many neurotransmitters and other signaling molecules, including oxytocin (Klatt and Goodson, 2013;Pedersen and Tomaszycki, 2012), vasopressin (Goodson et al, 2004), cortisol (LaPlante et al, 2014, hormones (Prior and Soma, 2015) and dopamine (Adkins-Regan, 2009;Banerjee et al, 2013;Goodson et al, 2009;Iwasaki et al, 2014;Tokarev et al, 2017).…”
Section: Introductionmentioning
confidence: 99%